1985
DOI: 10.1128/aac.27.1.132
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of intra- and extracellular Mycobacterium avium-intracellulare to cephem antibiotics

Abstract: Intra-and extracellular susceptibility of 35 clinically isolated Mycobacterium avium-intracellulare strains to cefotaxime (CTX), ceftizoxime (CZX), and cefoperazone was studied. MICs for 50% of the isolates in vitro were 6.25 ,Ig/mI for CTX and CZX and 25 ,ug/ml for cefoperazone. A strain susceptible to CTX (MIC, 0.78 ,ug/ml) and CZX (MIC, 1.56 ,ug/ml) infected human peripheral blood mononuclear cells in the presence of 20% autologous plasma. The mycobacteria replicated exclusively in monocytes under the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Dapsone (164,177) and sulfamethoxazole (168) have minimal antimycobacterial activity in vitro and may contribute to reductions in mycobacteremia in certain patients. In addition, there has been renewed interest in the minimal antimycobacterial activity seen with some beta-lactam antibiotics (78,117,360,491).…”
Section: Therapeutic Agents and Treatmentmentioning
confidence: 99%
“…Dapsone (164,177) and sulfamethoxazole (168) have minimal antimycobacterial activity in vitro and may contribute to reductions in mycobacteremia in certain patients. In addition, there has been renewed interest in the minimal antimycobacterial activity seen with some beta-lactam antibiotics (78,117,360,491).…”
Section: Therapeutic Agents and Treatmentmentioning
confidence: 99%
“…Dapsone (164, 177) and sulfamethoxazole (168) have minimal antimycobacterial activity in vitro and may contribute to reductions in mycobacteremia in certain patients. In addition, there has been renewed interest in the minimal antimycobacterial activity seen with some beta-lactam antibiotics (78,117,360,491).…”
Section: Therapeutic Agents and Treatmentmentioning
confidence: 99%
“…More recently, primary cell assays have been used only in confirmatory studies [ 35 ]. In the past, there were numerous researches to investigate drug efficacy in human peripheral blood mononuclear cells (PBMCs) [ 30 , 44 , 45 , 46 , 47 , 48 ]. For studies involving mice, primary bone marrow-derived macrophages have been preferred to other primary cell cultures [ 49 , 50 ], although some older studies have also suggested the use of zymosan A-induced murine peritoneal macrophages [ 51 , 52 ].…”
Section: Static Intracellular Infection Modelsmentioning
confidence: 99%